Formal search and referrals from a firm's perspective - Martina Rebien; Michael Stops; Anna Zaharieva (Bielefeld University, Center for Mathematical Economics (IMW), 2017)
This study explores the relationship between firms' characteristics and their recruitment strategies. We propose a model based on a search and matching framework with two search channels: a formal channel which is costly for firms and a costless informal channel, i.e. referrals. There is a continuum of heterogeneous vacancies in our model where every firm with an open vacancy chooses an optimal search effort in order to attract job candidates. This search effort depends on the productivity of the firm and, contrary to the previous literature, workers send simultaneous applications to open vacancies. We assess the model predictions by using the IAB Job Vacancy Survey, a representative survey among human resource managers in Germany reporting information about their most recent recruitment case. Based on the finding that firm size and productivity are positively correlated we show that: (1) Larger firms invest more effort into formal search activities; (2) Firms invest more formal search effort in labour markets for more educated workers; (3) The positive relationship between firm's size and formal search intensity can also be observed for firms that don't use referrals; (4) Firms that use referrals as a search channel invest less effort into formal search compared to firms that don't use referrals; (5) Larger firms are less likely to hire an applicant by referral than smaller firms, and (6) More intensive search effort leads to a larger number of applications.
urn:nbn:de:0070-pub-29143518
Keywords: J21; J23; J63; J64; 330; firm size; productivity heterogeneity; search effort; referrals; recruitment strategies